Suicide terrorism - Noor, Noraini M. (Wiley-Blackwell, 2012)
An encyclopedia entry detailing the meaning, history, and causes of suicide terrorism. In addition, the characteristics of suicide terrorists are highlighted and the entry ends with some ways of countering suicide terrorism.